EXPLORING COPPER CONTENT IN THE ENVIRONMENT OF KUNDILA, NIGERIA - AlKhatib, Ahed J; Muhammad, Murtala; Alhassan, A. J.; Habib, Ishaq.Y.; Bala, Sani Y.; Adamu, Auwal (European Scientific Journal, ESJ, 2014)
Copper is an important element in small quantities, and it is associated with adverse effects when its concentrations exceed normal limits. Its exploring in environment gives an idea about its disposition. The purpose of the present study was to explore the environment load of copper in soil, water, and vegetables at Kundila, Nigeria. To achieve study objective, water samples, soil samples, vegetable samples of lettuce, spinach, and onions were randomly taken. All samples were processed and prepared for assaying copper using atomic absorption spectrophotometer. Study findings indicated that copper concentrations in soil and water were within reference range, but the three vegetables under study had high concentration of copper.